The importance in clinical practice of the signal lymph node biopsy in squamous cell carcinoma of the head and neck - I. M. Gelfand; M. A. Kropotov; M. T. Isaeva; S. O. Podvyaznikov (Опухоли головы и шеи, 2024)
Skin cancer is the second most common tumor among non-melanoma malignant skin neoplasms, accounting for 20 % of cases. In the Russian federation in 2022, this pathology was identified in 79,124 people. The peak incidence occurs in the age range of 60–70 years. Considering the increasing life expectancy, the incidence of skin cancer is expected to rise. Despite the fact that regional metastases occur in 0.3–16 % of cases, the risk of metastasis can increase up to 48 % depending on high-risk factors. Since the presence of regional metastases is a key prognostic factor, special attention should be given to preventive interventions in the areas of regional metastasis.